Deformation mechanisms in amorphous Ni–Mo–P films coated on CoCrFeNi high-entropy alloys. (November 2019) - Song, X.T.; Guo, R.P.; Wang, Z.; Wang, X.J.; Yang, H.J.; Qiao, J.W.; Han, L.N.; Liaw, P.K.; Wu, Y.C.
Abstract: The Ni–Mo–P amorphous films were successfully deposited on the CoCrFeNi high-entropy alloys by electroless plating. This work will focus on reviewing and discussing the ambient-temperature mechanical properties, plastic deformation, and cracking mode of the coating-substrate system. The yielding strength (σy ) and ultimate tensile strength (UTS) of the specimen plating for 1 h were 260 and 760 MPa, respectively, with 44.4% (σy ) and 14.2% (UTS) improvement contrast to the uncoated HEAs (σy and UTS are 180 MPa and 560 MPa, respectively). It is attributed to the back stress and repulsive image stress to suppress the nucleation and mobility of dislocations. Due to the substrate confinement, the deformation model was gradually changed from cracking (with homogeneous flow) to shear banding (with homogeneous flow). Eventually, fully-homogeneous flows occur with reducing the film thickness, and the deformation mechanism map is developed to expound the transition of the deformation mode. The brittle fracture with a high velocity originating from amorphous films leads to cleavage cracking on the surface of the HEA substrate. The thicker film has higher crack velocity and causes deeper cracks penetration into the substrate, reducing the substrate ductility. Graphical abstract: In the coating-substrate system, with enhancing the film thickness, the substrate confinement effect and the adhesion are reduced, which causes that the ratio of the elastic energy in the amorphous film transferred to shear banding or cracking is decreased, which implies the size dependence of the deformation mode for Ni–Mo–P amorphous films in tension. The deformation mode of amorphous coating changes from fully-homogeneous to shear banding (with homogeneous flow), and eventually, the cracking (with homogeneous flow) dominates with increasing the coating thickness. Image 1 Highlights: The strength mechanism of Ni–Mo–P/CoCrFeNi system was proposed. A deformation map was delineated to reveal transition of deformation mode. The fracture of amorphous films induced the cleavage fracture in substrates.